Reviving performance by adopting chameleon style of leadership - Massoudi, Aram (Journal of Management and Business Education, 2022)
With new, diverse, and complicated challenges facing contemporary leaders in today’s ‎changing and distinct environment, it is essential for organizations to move away from ‎old and traditional leadership practices and embrace new ones. This study focused on ‎adopting the concept of “Chameleon Leadership”, the capacity to be able to amend ‎your tactics, much as a chameleon does to improve organizational performance. The ‎study relied on the descriptive deductive approach; this approach comprises of ‎formulating the hypotheses and tests them during the study process. The sample consists ‎of 126 randomly selected staff from various faculties at Albaath University, Syria. ‎The objective was to show if the adoption of chameleon leadership could improve ‎university performance. The result showed that there is a significant relationship between ‎‎the chameleon style of leadership ‎‎and outstanding university performance. Also, the adoption of chameleon leadership ‎characteristics can enable organizations to achieve outstanding performance in their ‎work. For success and development of chameleon operations, the ‎researcher suggested that universities must conduct extensive training about ‎chameleon leadership methods in line with the reality of the university despite the ‎existence of laws that hinder the development process.